Reading difficulties, their causes and treatment among students of the Arabic Language Department at the Faculty of Education at charmo University - Marwan Asaad Mohammed, Rese.; Frishta Hama Ahmed, Rese. (lark, 2025)
The research aims to determine the degree of reading difficulties faced by students in the Arabic Language Department at the College of Education at charmo University when teaching reading. The sample consisted of (30) students, including (8) males and (22) females, who were randomly selected from the third, fifth, and seventh semesters in the academic year (2024 - 2025). For the purposes of the study, the researchers developed an error tracking card for reading difficulties that included (9) reading difficulties. They also attempted to discuss the causes of these difficulties among students and provide appropriate solutions to address these challenges. In light of these results, the study concluded with a number of recommendations.
Keywords: Difficulties, Reading, University of charmo